Computational study of flow around a NACA 0012 by using Roe FVM scheme and davis-yee TVD scheme - Fatimah Yusop; Zamri Omar; Bambang Basuno; Nik Normunira Mat Hassan (Institute of Advanced Engineering and Science, 2019)
Currently CFD had been considered as an important tool for solving engineering problems. The application of CFD had been used intensively in aircraft industries in design a new aircraft or in the effort of improvement on the exiting aircraft. In term of CFD computer code, the CFD code differs with any others may due to the difference in the numerical scheme have been used. Therefore, the present work presents the comparison result between two developed computer codes with ANSYS-FLUENT software to the case of transonic steady flow past through airfoil NACA 0012. The first computer code used a finite difference method with numerical scheme according to Davis-Yee TVD scheme. Meanwhile, the second computer code used a Roe’s cell centre finite volume scheme. The flow analysis is carried out at two Mach number, M (0.65 & 0.8). Each Mach number applied to two different angles of attacks (0° & 5°). The flow domain discretized by use of C-topology with 193x63 grid points. The comparison in term of the pressure coefficient, along the airfoil surface are presented. From the result, indicated that developed computer code is able to capture the presence of shock wave in the flow field.